Judge's Managerial Competences: a Case Study of a High-Performance Court - Livia Lúcia Oliveira Borba; Fabricio Castagna Lunardi; Tomas Aquino Guimarães (Revista Direito GV)
Abstract This article investigates the managerial competences that are most important for state trial court judges in the performance of their managerial tasks, and the relationship between these competences and management practice. This topic has not been fully explored in the scientific literature and the present study employed a qualitative approach supported by interviews, and document analysis. The research is a case study of the trial court of Espinosa City, of the Minas Gerais State Court, Brazil. The performance of this court is outstanding when compared with other similar trial courts. We interviewed 13 key actors in that judicial unit, including four judges, the court secretariat manager, five officials, a social worker, a prosecutor, and a lawyer. Each interview was conducted using a semi-structured interview schedule. The data was assessed using content analysis, with the support of ATLAS.ti and Iramuteq software. The results evidence eight judges’ managerial competencies and one resource (support team expansion). The competences are the following: People Management and Team Leadership, Judicial Proceedings Management, Communication, Systemic Vision, Innovative Action, Information Management, Technical Managerial Competence, and Outcomes-Oriented Management. These results and their relationship with court performance are herein discussed. A research agenda, managerial implications and improvements in the Judiciary’s management policies are also set out.